Agreement between parent-report and EMR height, weight, and BMI among rural children - Potts, Benjamin A.; Wood, G. Craig; Bailey-Davis, Lisa (Frontiers in Nutrition, 2024)
Remote anthropometric surveillance has emerged as a strategy to accommodate lapses in growth monitoring for pediatricians during COVID-19. The purpose of this investigation was to validate parent-reported anthropometry, and inform acceptable remote measurement practices among rural, preschool-aged children.Methods: Parent-reported height, weight, BMI, BMI z-score, and BMI percentile for their child was collected through surveys with assessment of their source of home measure. Objective measures were collected by clinic staff at the child's well-child visit (WCV). Agreement was assessed with correlations, alongside exploration of time gap (TG) between parent-report and WCV to moderate agreement. Using parent-and objectively reported BMI z-score, weight classification agreement was evaluated. Correction equations were applied to parent-reported anthropometrics.Results: 55 subjects were included in this study. Significant differences were observed between parent-and objectively reported weight in the overall group (-0.24 kg; p=0.05), as well as height (-1.8 cm; p=0.01) and BMI (0.4 kg/m2; p=0.02) in the ≤7d TG + Direct group. Parental reporting of child anthropometry ≤7d from their WCV with direct measurements yielded the strongest correlations (r=.99 (weight), r=.95 (height), r=.82 (BMI), r=.71 (BMIz), and r=.68 (BMI percentile)) and greatest classification agreement among all metrics (91.67% (weight), 54.17% (height), 83.33% (BMI), 91.67% (BMIz), and 33.33% (BMI percentile)). Corrections did not remarkably improve correlations.Discussion: Remote pediatric anthropometry is a valid supplement for clinical assessment, conditional on direct measurement within 7 days. Among rural populations where socioenvironmental barriers exist to care and surveillance, we highlight the utility of telemedicine for providers and researchers.